Comparison of Intraocular Pressure Lowering Effect of Travoprost and Timolol / Dorzolamide Combination in Primary Open Angle Glaucoma - Imran Ahmad, Farooq Khan, Mubashir Rehman, Omar Ilyas, Mohammad Zeeshan Tahir (Pakistan Journal of Ophthalmology, 2015)
Purpose: To compare the efficacy of once daily travoprost 0.004% and twice daily Timolol 0.5% plus dorzolamide 2% combination in primary open angle glaucoma. Material and Methods: This study was conducted at outpatient department, Ophthalmology unit, Khyber Teaching Hospital, Peshawar. Study design was randomized controlled trial and (group B receiving Timolol 0.5% and Dorzolamide 2% was considered as control group) the duration of the study was 6 months in which a total of 136 patients were included. All cases included in the study were diagnosed as cases of primary open angle glaucoma. Patients were divided into two groups i.e. A and B with each group having 68 patients. Patients in group A were given Travoprost 0.004% eye drops daily and patients in group B were given eye drops having combination of Timolol 0.5% and Dorzolomide 2% twice daily. Patients were advised to come at 6 weeks interval for follow up. At each follow up visit, IOP was recorded. Results: Mean age in Group A was 53 ± 13.26 years while in Group B was 55 ± 14.31 years. In Group A 56% patients were male and 44% patients were female where as in Group B 59% patients were male and 41% patients were female. Our results show that Timolol + Dorzolamide was more effective than Travoprost as Timolol + Dorzolamide cause reduction in IOP of at least 20% in 84% patients while Travoprost cause reduction in IOP of at least 20% in 80% patients. Also pvalue calculated at six week is statistically significant). Conclusion: Our study concludes that dorzolamide with timolol is more efficacious than Travoprost in open angle glaucoma. Key Words: Primary open angle glaucoma, travoprost, Timolol plus dorzolamide.